Comprehensive Study and effect of Immigration Law on Family Relationships - Dr. Anil Vats (International Journal of Medical Toxicology and Legal Medicine, 2024)
The research examines how various aspects of immigration laws influence family relationships by studying how the law interacts with cross-border experiences of the families. The law on immigration receives very keen interest in whose family members will reunite through what conditions and expresses how long such a reunification will take. This study would try to learn the socio-legal, psychological, and emotional consequences of immigration policies over families, mainly in the contexts of deportation, detention, or delay in family sponsorship. Employing qualitative methodologies, this research paper analyses the secondary data with peer-reviewed articles, legal documents, and reports of international organizations published within the last five years. It includes Bronfenbrenner’s Ecological Systems Theory and Social Capital Theory in explaining how laws marginalize family life. In the end, immigration laws that are considered very stringent tend to lead to much more emotional distress, instability, and long-term separation from families. The brunt of these effects is borne by children, as often their development will be affected due to disrupted family environments. Finally, this research paper throws recommendations toward a humane immigration reform. These include uniformity in legal practice, fast-tracking reunion, and trauma-informed legal services provision. In sum, this research adds to the existing literature in human rights and immigration justice, using this forum to implore policy-makers to factor family integrity as a core sterling in any humane migration policy.